(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The history of freedom movement would be incomplete without mentioning the contributions of women. The sacrifice made by the women of Karnataka will occupy the foremost place. They fought with true spirit and hardships to undaunted courage and faced various tortures, exploitations and hardships to earn us freedom. When most of the men freedom fighters were in prison the women came forward and took charge of the struggle. The list of great women whose names have gone down in history for their dedication and undying devotion to the service of Karnataka is a long one.